Consumption patterns and key motivational drivers: an analysis of food behavior in Spanish households - Beltrán-de-Miguel, Beatriz; del-Pozo-de-la-Calle, Susana; Cuadrado-Vives, Carmen; Ruiz-Moreno, Emma (Frontiers in Nutrition, 2025)
Background/objectivesBased on data collected in a market study, this analysis examines the food consumption patterns of Spanish households and the main individual motivations behind the use of these foods in each consumption occasion.MethodsA descriptive cross-sectional observational study was conducted using the “Household Usage Panel” (2023). Individual food consumption at home was recorded through an online survey over the course of a full week, twice a year, throughout the year. For each consumption occasion, the primary reason for the food choice was also recorded, selected from predefined options: “product was available,” “for health,” “by habit,” “taste,” “for pleasure/I felt like it,” and “quick/easy to prepare.”ResultsThe sample included 5,207 individuals (4,000 households), representative of the Spanish population, excluding the Canary Islands, Ceuta, and Melilla. The food groups used by more than 80% of the panelists include cereals and cereal products, vegetables, meat, fish, milk and dairy products, and fruit. For all products combined, 80.2% of consumers reported that, on at least one consumption occasion, the primary reason for use was “for taste,” 77.1% “for pleasure/I felt like it” followed by “health” (68.4%), “product was available” (59.2%), “habit” (55.3%), and “quick/easy to prepare” (47.6%). For each food group, the primary reason for use varied by occasion, with “for taste” and “for pleasure/I felt like it” chosen by a higher percentage of consumers. An exception was found with the fruit and olive oil groups, where the main reason for consumption chosen by a larger percentage of consumers on some occasions was health (57.4 and 30.8%, respectively).ConclusionUnderstanding the motives behind food consumption in Spanish households helps us better grasp specific dietary behaviors. Taste and pleasure have been identified in this study as key factors in food choices at home. These insights suggest the need for a renewed approach to food policies and interventions that promote healthy eating, with the potential for lasting improvements in dietary quality over the medium to long term.